The psychological journey to and from loneliness : development, causes, and effects of social and emotional isolation - Rokach, Ami (Academic Press, 2019)
There are three universal experiences that we cannot escape: loneliness, illness, and death. The Psychological Journey To and From Loneliness addresses what was termed the plague of the 21st century--loneliness. Loneliness is stigmatized in our society, so untold number of people walk around lonely, unable to do what is so naturally called for--make their suffering known, and approach others for company and support. Thankfully, loneliness is slowly, but steadily, coming out of the "closet." This book will highlight not only the experience and what can be done about it, but also the experiences that influence it (i.e., our childhood, cultural and religious influences, and our way of life) as well as the effects that loneliness has on various population groups and how it is experienced at different times in our lives. This volume reviews theoretical approaches to the study of loneliness: the (positive) functions that loneliness may serve in our lives; the stages in life when loneliness is quite "visible" and its effects on us; the life experiences that may strengthen the feeling that one is all alone and forgotten; life experiences that we do not commonly connect to loneliness but it is clearly present in them (e.g., pregnancy and childbirth); and the approaches that are available to copy with its pain and limit its negative effects on us. The book closes with a review of how psychotherapy can assist those who need encouragement and support in their struggle with loneliness. The book is particularly suitable for academics, researchers, and clinicians who aim to help clients identify, address, and cope with loneliness